Citizen's Adoption Of Mobile Land Record Information Systems (mLRMIS): A Case of Pakistan - Babur Hayat Malik; Cai Shuqin; Abdul Ghaffar Mastoi; Ahmed Hussein Alsherbiny Ahmed Ghais (European Scientific Journal, ESJ, 2016)
By implementing a prolonged social cognitive theory (SCT) this article investigates factors including outcome expectation, affect, anxiety, self-efficacy, social influence, trust, facilitating conditions, e-satisfaction, information quality and e-service quality impacting citizen’s intention to adopt a mobile based e-government system called mobile Land Record Information Systems (mLRMIS) with respect to Pakistan. The prolonged social cognitive theory (SCT) was actually affirmed by analyzing gathered data periodically accumulated over time from 10 different cities in Pakistan. Verifiable results of the proposed model represented mutual significance of relationships of 12 hypothesized relations between 10 different types of constructs. Only a few studies have previously used SCT model to investigate the adoption of an e-government system globally while in case of Pakistan it is the first ever study using SCT model to figure out the adoption of an e-government system. Outcome significance and digital policy substance exhibited in this article can assist e-government planners and practitioners to reform up quality and effectivity of mLRMIS system. This research also contributes to elevate relevant awareness and utilization of mLRMIS system.